2012
DOI: 10.5762/kais.2012.13.6.2579
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Fatigue, Family Function and Self-esteem of Middle-aged Women in Menopausal Periods

Abstract: The purpose of this study was to examine the relations between fatigue, family function and self-esteem among middle-aged women in menopausal periods. Data were collected through self-administered questionnaire survey form 133 middle-aged women. The data collection was done from March 2nd to April 10th, 2012. As a results, there were significant differences in fatigue by education level and menstrual status. And, there were significant differences in family function according to education level and marital sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…For middle-aged and older women with healthy bodies, in addition to high living standards and high self-esteem, they were also found to have good mental health. 15 It is reported that self-esteem in middle age is an important factor in determining the QOL in old age. Middle-aged women with low self-esteem were also characterized by low health promotion and lifestyle transition, high levels of depression and anxiety, social isolation, lack of self-confidence, and fear of failure.…”
Section: Middle-aged and Older Women's Appearance Satisfaction And Se...mentioning
confidence: 99%
“…For middle-aged and older women with healthy bodies, in addition to high living standards and high self-esteem, they were also found to have good mental health. 15 It is reported that self-esteem in middle age is an important factor in determining the QOL in old age. Middle-aged women with low self-esteem were also characterized by low health promotion and lifestyle transition, high levels of depression and anxiety, social isolation, lack of self-confidence, and fear of failure.…”
Section: Middle-aged and Older Women's Appearance Satisfaction And Se...mentioning
confidence: 99%